110k views
0 votes
Gla)=a-4
Ha)=a* +2-a
Find gla). Mla)

Gla)=a-4 Ha)=a* +2-a Find gla). Mla)-example-1
User Lieven
by
5.8k points

2 Answers

5 votes

Answer:

a³ - 5a² + 6a - 8

Explanation:

Given we require

g(a) × h(a)

= (a - 4)(a² + 2 - a)

Each term in the second factor is multiplied by each term in the first factor, that is

a(a² + 2 - a) - 4(a² + 2 - a) ← distribute both parenthesis

= a³ + 2a - a² - 4a² - 8 + 4a ← collect like terms

= a³ - 5a² + 6a - 8 ← in standard form

User Tturbo
by
4.8k points
4 votes

Answer:

2

Explanation:

a is 2 so 2+2=4 and 4-2=2 so the answer would be 2.

User JenyaKh
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.